A Timely Revolution: Reflecting on the Promise and Challenges of a New Diagnostic Tool for Medical Emergencies - Rahman, Md Zakiur (Journal of Brahmanbaria Medical College, 2026)
Abstract not available Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 1-2